(untitled) (Research, Society and Development, 2021)
Differential and Integral Calculus is the part of Mathematics that takes care of, among other topics, the study of the rates of variation of quantities. Mathematics is present in everyday life more than one can imagine and, through a brief study, it can be seen that it contributes to our daily activities, whether in basic operations, when calculating the change for money when we sell something, or in situations where more complex calculations are required. The Discipline of Differential and Integral Calculus must dialogue with the professions, and one of the causes of the students’ lack of interest is associated with the absence of an applied view of the content in the professional career activity. In view of this, this work proposes to present and discuss five examples of applications of Differential and Integral Calculus in Science and Engineering. The methodology used is exploratory, based on a bibliographic survey. It is expected, therefore, to contribute to the teaching of themes related to Differential and Integral Calculus, pointing out applications of its use in different areas of knowledge.